2014
DOI: 10.1080/15402002.2014.941064
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Psychosocial Functioning, and Device-Specific Adjustment in Patients with Implantable Cardioverter Defibrillators (ICDs)

Abstract: Rates of sleep disorders and associated adjustment were examined in patients with implantable cardioverter defibrillators (ICDs; n=42; Mage=61.57, SD=12.60). One night of ambulatory polysomnography, 14-days of sleep diaries, and questionnaires (mood, sleepiness, fatigue, device acceptance) were administered. MANCOVA (controlling for ischemia) examined adjustment by sleep diagnosis. Apnea was most common-28.6%, followed by Insomnia-16.7% and Comorbid Insomnia/Apnea-11.9%. Patients with insomnia reported poorer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“… 5 , 6 In turn, this may lead to impaired QoL, adverse cardiovascular outcomes and perhaps sleep disturbances. 7 9 Particularly, patients with a Type D (distressed) personality (combination of high negative affectivity and high social inhibition) are prone to experience adverse health outcomes post-implantation. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 , 6 In turn, this may lead to impaired QoL, adverse cardiovascular outcomes and perhaps sleep disturbances. 7 9 Particularly, patients with a Type D (distressed) personality (combination of high negative affectivity and high social inhibition) are prone to experience adverse health outcomes post-implantation. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…A Danish study found clinically significant sleep problems in up to 67% of patients. 12 One American study found that patients with ICD and co-morbid sleep problems reported increased fatigue, decreased mood and poorer device acceptance, 8 while a small study using actigraphy that measures sleep efficiency by means of sleep/wake cycles found that ICD patients had better sleep efficiency than cardiac patients without an ICD. 13 This is somewhat in line with a recent meta-analysis revealing that sleep disordered breathing is associated with an increased incidence of appropriate ICD therapy only in patients with heart failure and reduced ejection fraction.…”
Section: Introductionmentioning
confidence: 99%
“…For patients who have had an ICD implanted-who should be referred for CR-there is as additional overlay of need. They have higher levels of health-compromising anxiety and depression, low levels of social support (Pedersen et al, 2009c), and high levels of sleep disorders (McCrae et al, 2016), with partners being highly affected by the patients' condition.…”
Section: Recommendationsmentioning
confidence: 99%
“…[ 4 ] However, the implantation of ICDs is associated with a reduced quality of life[ 5 ] and the development of mood disorders. [ 6 ] Therefore, patients living with ICD experience a high rate of insomnia,[ 7 ] depression and anxiety,[ 8 ] and stress. [ 9 ] Furthermore, patients after ICD placement may show fear,[ 10 ] feelings of loneliness and lack of support,[ 11 ] self-restrictions on physical activity,[ 12 ]feeling of an involuntary job move,[ 13 ] worries about their future,[ 14 ] communication restrictions,[ 15 ] and the unpleasant feeling when the shock is discharged.…”
Section: Introductionmentioning
confidence: 99%